Translation Techniques Used in Translating Cooperative Principle in the Speech of a Tourette Syndrome Character in Motherless Brooklyn - Angraini, Melina; Nababan, M. R.; Yustanto, Henry (Pioneer: Journal of Language and Literature, 2025)
This study aims to analyze how the cooperative principle is translated in the response utterances of a character with Tourette syndrome in the novel Motherless Brooklyn. The research uses a descriptive qualitative method with a product-oriented focus. The data sources include the novel itself and raters who evaluate the translation. The data consist of linguistic features and aspects of translation. Data were collected through document analysis and Focus Group Discussions (FGD). The study applies an ethnographic approach, using Spradley’s method for data analysis. The findings reveal that the utterances influenced by Tourette syndrome result in noticeable shifts in translation. Two primary patterns of conversational maxim violations were identified. The first pattern is caused by the symptoms of Tourette syndrome, including echolalia, coprolalia, and palilalia, which disrupt typical patterns of speech. The second pattern involves deliberate maxim violations driven by specific communicative intentions. These findings highlight the complexity of translating neurodivergent speech and emphasize the importance of contextual and pragmatic awareness in maintaining the speaker’s original meaning and intent.